The Surface Charge of Isolated Toad Bladder Epithelial Cells : Mobility, effect of pH and divalent ions - Lipman, Kenneth M. (The Rockefeller University Press, 1966)
The surface charge of epithelial cells isolated from the toad bladder has been determined by the microscope method of cell electrophoresis. The cells possess a net negative charge, and a net surface charge density of 3.6 x 10(4) electronic charges per square micron at pH 7.3. Estimates of net surface charge over the alkaline pH range indicate (a) that an average distance of the order of 40 A separates the negatively charged groups, and (b) that amino as well as acid groups are present at the electrophoretic surface of shear. A significant increase in mobility following cyanate treatment of the cells suggests that a large proportion of the amino groups are the ε-amino groups of lysine. In view of the known effects of calcium and other divalent ions on cell permeability and cell adhesion, the extent of binding of calcium and magnesium to the cell surface was determined by the electrophoretic technique. Mobility was significantly decreased in the presence of calcium or magnesium, indicating that these ions are bound by surface groups. When the pH was lowered from 7.3 to 5.2, calcium binding was markedly decreased, an observation consistent with competition between calcium and hydrogen ions for a common receptor site.